Students’ readiness in the use of technology for rural elementary schools - Latifah, Siti; Sujarwo, Sujarwo (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2023)
The research aims to determine the eff ect of theuse of technology rural elementary schools in Yogyakarta. The quantitative research method was in the form of a survey at four elementary schools with the best National Examination scores based on ASPD 2021/2022, favorite schools in Kretek, schools accepted inclusive students, and disciplinary schools. Research subjects were fourth grade elementary school students, the instrument is a technology readiness questionnaire and secondary data on learning outcomes in the form of one semester report card grades. Data collection includes questionnaires and documentation,data were taken using descriptive and inferential statistics. The results presented that there was an eff ect of the use of technology on the learning outcomes of elementary school students. It is known that the sig value for technology normality, learning outcomes, the technology linearity test value and learning outcomes, as well as hypothesis was tested using a simple linear regression. Based on the calculation, the Ho was rejected and HÎ± was accepted.